PENGARUH KINERJA KEUANGAN DAN CORPORATE SOCIAl RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Joseph, Angelika Natalia; Poputra, Agus T.; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
The financial performance is an image of a quality company that is reflected through the financial performance in a given period. Corporate Social Responsibility (CSR) is the ability of the company to connect its operations and policies of the social environment in a way that is mutually beneficial for the company and the community. The company's value is the market value as the value of the company can deliver maximum shareholder wealth when the company's stock price to rise. The purpose of this study was to analyze the influence of corporate social responsibility (CSR), and the financial performance of the company's value. Object Manufacturing research company that totaled 143 company, but based on the completeness of data then only 18 companies into the sample with the observation period 2012 - 2015. The independent variables were the company's performance (return on assets, return on equity, Operating Profit Margin, Net Profit Margin) and Corporate Responsibility Cocial, while the enterprise value of the dependent variable (Price Book value). Analysis of the data used consisted of correlation analysis, determination analysis, t-test, f, and multiple linear regression analysis. The results of this study indicate that ROA and ROE have a significant influence on the value of the company, while OPM, NPM, and CSR does not have a significant influence on the value of the company. F test analysis results indicate that the independent variables namely financial performance and CSR affect the value of the company. Â  Keywords : corporate value, corporate social responsibility, corporate performance